Recent development of advanced biotechnology for wastewater treatment. (2nd January 2020) - Yi, Huan; Li, Minfang; Huo, Xiuqin; Zeng, Guangming; Lai, Cui; Huang, Danlian; An, Ziwen; Qin, Lei; Liu, Xigui; Li, Bisheng; Liu, Shiyu; Fu, Yukui; et al.
Abstract: The importance of highly efficient wastewater treatment is evident from aggravated water crises. With the development of green technology, wastewater treatment is required in an eco-friendly manner. Biotechnology is a promising solution to address this problem, including treatment and monitoring processes. The main directions and differences in biotreatment process are related to the surrounding environmental conditions, biological processes, and the type of microorganisms. It is significant to find suitable biotreatment methods to meet the specific requirements for practical situations. In this review, we first provide a comprehensive overview of optimized biotreatment processes for treating wastewater during different conditions. Both the advantages and disadvantages of these biotechnologies are discussed at length, along with their application scope. Then, we elaborated on recent developments of advanced biosensors (i.e. optical, electrochemical, and other biosensors) for monitoring processes. Finally, we discuss the limitations and perspectives of biological methods and biosensors applied in wastewater treatment. Overall, this review aims to project a rapid developmental path showing a broad vision of recent biotechnologies, applications, challenges, and opportunities for scholars in biotechnological fields for "green" wastewater treatment.